PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERAWATAN DIRI PENDERITA DIABETES MELLITUS TIPE 2 DI PUSKESMAS PANDAK I - Ferianto; Mateus Sakundarno Adi; Nurullya Rachma (MEDIA ILMU KESEHATAN, 2019)
Background: Someone in middle adulthood has begun to experience changes leading to an aging process, so they are vulnerable to degenerative diseases. Diabetes mellitus is a degenerative disease which is still being a health problem in Indonesia. Problems and complications in people with DM can be minimized if the patient has sufficient knowledge and ability to carry out self-care. One effort that can be done is to provide health education about self-care to optimize metabolic control, prevent acute and chronic complications, optimize quality of life and able to carry out self-care behavior independently. Objective: The study aimed to determine the effect of health education on self-care activities in type 2 diabetes mellitus in Puskesmas Pandak I. Methods: This was a quasi-experimental study with a one group pretest-posttest study design. The samples used were 26 respondents. Data analysis technique used paired t-test with a significance level of p <0,05. Results: There is a significant enhancement in self-care activities. Statistical analysis using paired t-test found there were significant differences in the value of self-care activities between pre and post-education among type 2 diabetes mellitus diabetes (p <0,005). Conclusion: Health education can improve self-care activities for people with type 2 diabetes mellitus in Puskesmas Pandak I. Keywords : Health education, self-care, diabetes mellitus